2000
DOI: 10.1128/jb.182.13.3740-3747.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of the dpr Product in Oxygen Tolerance in Streptococcus mutans

Abstract: We have previously identified and characterized the alkyl hydroperoxide reductase of Streptococcus mutans, which consists of two components, Nox-1 and AhpC. Deletion of both nox-1 and ahpC had no effect on the sensitivity of S. mutans to cumene hydroperoxide or H 2 O 2 , implying that the existence of another antioxidant system(s) independent of the Nox-1-AhpC system compensates for the deficiency. Here, a new antioxidant gene (dpr for Dps-like peroxide resistance gene) was isolated from the S. mutans chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
106
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 44 publications
7
106
0
3
Order By: Relevance
“…The digested PCR products were cloned into pCKR101 vector to generate the pDpr plasmid. Overproduction of active Dpr protein was confirmed by native PAGE stained with Ferene S (26 To avoid interactions between iron and conventional buffering compounds, none were used. Instead, solutions were adjusted with dilute NaOH to the desired pH, and the pH of the reaction solution was measured at the conclusion of the reaction to verify that it had not changed significantly (Ͻ0.2 pH units) (14).…”
Section: Methodsmentioning
confidence: 99%
“…The digested PCR products were cloned into pCKR101 vector to generate the pDpr plasmid. Overproduction of active Dpr protein was confirmed by native PAGE stained with Ferene S (26 To avoid interactions between iron and conventional buffering compounds, none were used. Instead, solutions were adjusted with dilute NaOH to the desired pH, and the pH of the reaction solution was measured at the conclusion of the reaction to verify that it had not changed significantly (Ͻ0.2 pH units) (14).…”
Section: Methodsmentioning
confidence: 99%
“…Dps family members share a conserved amino acid motif, similar to mammalian ferritin L-subunit iron nucleation center, in the N-terminal halves of the proteins (14,(22)(23)(24). Because several members, including the streptococcal Dpr (11,25), are known to bind iron (17,22,26,27), the conserved motif is believed to serve a functional role. It has been suggested that the motif catalyzes iron oxidation by its putative ferroxidase activity and also directs the formation of an iron core into the inner cavity of the oligomer (17,22,28,29).…”
mentioning
confidence: 99%
“…Gram-positive bacteria, including the important human pathogens Streptococcus pyogenes and Streptococcus pneumoniae (11), relatively little is known of the molecular mechanisms of its action. The primary amino acid sequence shares similarity with Escherichia coli Dps (DNA-binding protein from starved cells) (12,13), a prototype for a large group of similar oligomeric proteins (14), which is abundantly expressed in starved cells and involved in DNA protection by DNA-Dps biocrystal formation (15,16).…”
mentioning
confidence: 99%
“…In this study, the subunit dissociation, DNA binding, and protection properties of native, untagged M. smegmatis Dps (DpsMs) 2 were assessed in parallel with those of the tagged protein (DpsMs-His) to establish possible differences between the two proteins ascribable to the C-terminal tag. Untagged and tagged dodecamers dissociated into dimers in a similar fashion.…”
mentioning
confidence: 99%
“…The proteins of the Dps (DNA-binding proteins from starved cells) family are expressed by most bacteria under a variety of stress conditions to protect DNA against oxidative damage and other detrimental factors (1)(2)(3). DNA protection is achieved by a dual action.…”
mentioning
confidence: 99%